PENGUATAN JATI DIRI BANGSA MELALUI PENGKADERAN ORGANISASI EKSTRA KAMPUS - Darda Abdullah Sjam, - (2022)
The Islamic Student Association (HMI) is an extra-campus organization that has produced quality cadres and has been active in many important institutions, including the government. However, HMI cadres are facing problems at this time due to the premature age of cadres, as well as the influence of globalization, and even ideologies of intolerance that have begun to absorb in educational institutions, especially universities. This study seeks to describe the strengthening of national identity through the formation of the extra-campus organization of the Islamic Student Association. The approach used is qualitative with case study method. The informants amounted to 39 people consisting of 6 people of Master of Training (MOT), 33 people of HMI Cadre. The research location is in the Bandung Islamic Association Branch Manager. The results of the study illustrate that (1) the understanding of the Bandung Branch HMI cadres towards national identity has shown positive results. Based on research results sourced from HMI cadres, it proves that most cadres can understand the concept of national identity that is learned at every level of cadre. In addition, the content of HMI cadre materials related to strengthening national identity resulted in increased understanding of cadres which can then be oriented in daily life; (2). HMI has a systematic cadre pattern and concept with standard guidelines, the HMI cadre concept is updated according to the results of the congress at each period. The cadre process carried out is largely determined by the quality of the management as the person in charge of developing the quality of cadres; (3). The HMI cadre model is considered good and effective in strengthening identity. However, other things that need attention are the development of cadres that need to be improved and carried out consistently, and the need for a monitoring system for cadre development to maintain the identity that has been embedded in each cadre. Keywords; National identity, cadre model, organization, Islamic student association.